IMPLIKASI PENYANDINGAN SALAT DAN ZAKAT PERSPEKTIF SEMIOTIKA - Hariani, Hidayah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
The Qur'an has the structure and rules of language that are part of its i'jaz (miracle). It has a deep meaning, even a secret in every syntactic structure. One of them is the mention of salat and zakat in many verses. The mention of these two services suggests that certain objectives are not merely literal interpretations. Therefore, in-depth studies are needed to look for reason and meaning contained therein. To achieve this goal, this research uses the semiotics method, which emphasizes its discussion on the sign system to look for the meaning that is in the marker. From searches conducted related to the theme of the discussion, 27 verses were found that contain the words salat and zakat together in one place. The verses are found in one concept, which is about faith in God. Nevertheless, the mention of salat and zakat in various verses has a different context. First, concerning the Children of Israel. Second, regarding the formation of faith through deeds. Third, the context related to jihad efforts. Fourth, signs of believers. Fifth, efforts to repent. And sixth, as an intermediary get mercy. This study also found that the mention of salat and zakat together and related to the element of faith indicated that salat and zakat were suggestions for connecting God, humans, and society in a circle. This shows that this study provides a reinforcing argument in the arguments of Toshihiko Izutsu.